Perceived impact of the COVID-19 pandemic on infection containment training and mental state of dental residents in China: A longitudinal study - Dai, Lina; Jiang, Dan; Wen, Qin; Zhang, Ximu; Song, Jinlin (Frontiers in Public Health, 2022)
COVID-19 has presented a challenge for dental settings and dental schools: how to continue providing dental care and maintain education during the pandemic while remaining healthy. This paper may also serve as a health policy reference for policy makers. The study aimed to compare the forms, frequency, contents, emphasis and test scores of infection containment control training pre- and post-pandemic. Besides,after the COVID-19 outbreak,we assessed the increased anxiety level,communication difficulties and confidence of dental residents impacted by the pandemic. A total of 251 dental residents in Stomatological Hospital of Chongqing Medical University were recruited to complete a questionnaire of their routine involvement in infection control training before and after the COVID-19 outbreak. A self-designed 10-point likert scale was used to assess the increased anxiety level,communication difficulties and confidence in facing with the future public health crisis impacted by the pandemic. After the outbreak, although more trainees chose online assessment than offline assessment, most of them (74.90%) still preferred in-person training rather than online training. Contents that trainees had been focusing on were affected by the COVID-19 outbreak. Thereafter, they were more inclined to learn crisis management. Over half of the respondents (56.17%) participated in training more frequently after the outbreak. However, postgraduate students participated in training less frequently than others after the outbreak (p < 0.01). First year trainees accounted for the majority in the population who emphasized considerably on infection control training and whose test scores had increased after the outbreak. In addition, the percentage of females scoring increasingly in post-pandemic assessment was significantly higher than that of males. In this study, the average increased anxiety level caused by COVID-19 was 5.51±2.984, which was positively related to communication difficulties with patients caused by the pandemic. Trainees from Hubei Province showed higher increased anxiety levels (8.29±2.93) impacted by thepandemic than trainees from other provinces (p < 0.05). However, the former’s confidence in coping with future public health crises was not significantly different from that of others (p > 0.05).